2019
DOI: 10.1097/md.0000000000014611
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and modifiable resuscitative characteristics amongst pan-Asian out-of-hospital cardiac arrest occurring at night

Abstract: Studies are divided on the effect of day-night temporal differences on clinical outcomes in out-of-hospital cardiac arrest (OHCA). This study aimed to elucidate any differences in OHCA survival between day and night occurrence, and the factors associated with differences in survival.This was a prospective, observational study of OHCA cases across multinational Pan-Asian sites. Cases were divided according to time call received by dispatch centers into day (0700H–1900H) and night (1900H–0659H). Primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
(41 reference statements)
1
20
0
Order By: Relevance
“…Prehospital de brillation was also a prognostic factor for OHCA [2,10]. Our study found that prehospital de brillation was associated with a higher chance of survival for the younger group than that for the older group.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Prehospital de brillation was also a prognostic factor for OHCA [2,10]. Our study found that prehospital de brillation was associated with a higher chance of survival for the younger group than that for the older group.…”
Section: Discussionsupporting
confidence: 47%
“…The prognosis of out-of-hospital cardiac arrest (OHCA) is very poor, with the survival rate ranging from 2-11% in the Asia-Paci c area [1]. Many prehospital factors in uence the outcomes of OHCA, such as witnessing the OHCA, bystander cardiopulmonary resuscitation (CPR), initial heart rhythm, level of hospital care, location, and time of OHCA [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Non-cardiac aetiologies included respiratory conditions, electrocution, drowning and other causes such as cancer and renal disease. Covariates were determined based on a literature review of possible confounders and/or known prognostic factors, [15][16][17][18][19] and were adjusted for in regression analyses. For presumed cardiac and non-cardiac aetiologies, 2 multivariate models were constructed to reflect postulated differences in incidence of aetiologies in NH and non-NH groups and different prognosticating factors.…”
Section: Methodsmentioning
confidence: 99%
“…As prehospital defibrillation and CPR performed by EMS/private ambulance are of significance in reducing mortality, possible measures to increase these may be to educate lay people on where to find and use automated external defibrillators and to regularly ensure our paramedics are up-to-date with their CPR skills. 25 These findings as a whole strongly support a focus on basic life support measures through community and prehospital intervention to increase prompt and effective CPR and automated external defibrillator use, which have far greater effect on outcomes. [25][26][27] Although there was some suggestion that TTM improved mortality and CPC in our study population, there was insufficient power to demonstrate statistical significance.…”
Section: Resultsmentioning
confidence: 79%
“…25 These findings as a whole strongly support a focus on basic life support measures through community and prehospital intervention to increase prompt and effective CPR and automated external defibrillator use, which have far greater effect on outcomes. [25][26][27] Although there was some suggestion that TTM improved mortality and CPC in our study population, there was insufficient power to demonstrate statistical significance. We postulate that TTM may not have been complete in many patients and complications may not have been accounted for.…”
Section: Resultsmentioning
confidence: 79%